Interaction between MTM and EGAM for energy and particle confinement improvements on HL-3 tokamak - S.Q. Wang; X.L. Zou; X.R. Duan; A.S. Liang; L.M. Yu; G.L. Xiao; Y.R. Zhu; M.K. Han; Y. Zhou; T.F. Sun; A. Wang; S.B. Gong; et al. (Nuclear Fusion)
We report the first observation of microtearing mode (MTM) and its interaction with energetic-particle-induced geodesic acoustic mode (EGAM) in the reduction of ambient turbulence, leading to improvements in energy and particle confinements in electron cyclotron resonance heating (ECRH) plasma on HL-3 tokamak. MTM, observed in the magnetic fluctuation spectrum with a frequency range of 80–120 kHz, is found to be driven by the electron temperature gradient. It has been shown that MTM propagates in the electron diamagnetic drift direction with a poloidal normalized wavenumber $0.05 \le {k_θ }{ρ _s} \le 0.17$ . The $n = 0,\,m = - 2$ magnetic structure of EGAM with a frequency range of 14–20 kHz is observed in the magnetic fluctuation spectrum, where n and m are the toroidal and poloidal mode numbers, respectively. The ${V_{E × B}}$ oscillation of EGAM has also been observed in the Doppler reflectometry phase derivative perturbation spectrum. The frequency of EGAM corresponds to half that of the conventional GAM. Bispectral analysis during ECRH shows pairwise interactions among EGAM, MTM and ambient turbulence (low frequency). It has been found that the reduction of ambient turbulence due to MTM and EGAM leads to the improvement of particle and energy confinements. Experimental results on HL-3 show that the interaction between MTM and EGAM provides a possible way to the turbulence control for energy and particle confinement improvements in future reactors.